2015
DOI: 10.1182/blood-2014-09-603464
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of CD4 T cells in PF4/heparin antibody production in mice

Abstract: Antibodies specific for platelet factor 4 (PF4)/heparin complexes are central to the pathogenesis of heparin-induced thrombocytopenia. Marginal zone B cells appear to be the source of such antibodies, but whether T-cell help is required is unclear. Here, we showed that induction of PF4/heparin-specific antibodies by PF4/heparin complexes was markedly impaired in mice depleted of CD4 T cells by anti-CD4 antibodies. Furthermore, Rag1-deficient recipient mice produced PF4/heparin-specific antibodies upon PF4/hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…42 At the immune cell level, CD4 + T-helper cells play a critical role in the production of HIT antibodies while marginal zone B cells produce the relevant antibodies. 43 However, heparin exposure is not always necessary for some anti-PF4 antibody formation. 32 These results suggest that antibodies generated in the presence of heparin may be distinct from those generated in its absence, leading to the possibility that distinct or different immunologic determinants on platelets may lead to a HIT-like clinical presentation.…”
Section: Discussionmentioning
confidence: 99%
“…42 At the immune cell level, CD4 + T-helper cells play a critical role in the production of HIT antibodies while marginal zone B cells produce the relevant antibodies. 43 However, heparin exposure is not always necessary for some anti-PF4 antibody formation. 32 These results suggest that antibodies generated in the presence of heparin may be distinct from those generated in its absence, leading to the possibility that distinct or different immunologic determinants on platelets may lead to a HIT-like clinical presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, all B-and T-cells were originated from the Drd3 -/-(or Drd3 +/+ in the control group) BM. On the other hand, the 4:1 ratio (Rag1 -/--to-Drd3 -/or Rag1 -/--to-Drd3 +/+ ) in the donor BM [48] ensure that all the other hematopoietic lineages different from lymphocytes were predominantly originated from the Rag1 -/-BM, and therefore were Drd3 sufficient. To restrict genetic Drd3deficiency only to B-cells, irradiated µMT mice received a BM mix composed of 80% from µMT mice and 20% from Drd3 -/mice.…”
Section: Animalsmentioning
confidence: 99%
“…To address the role of DRD3 in the adaptive immune system in the development of CNS autoimmunity we generated chimeric mice bearing Drd3-deficient adaptive immune system and Drd3-sufficient innate immune system. For this purpose, recombination-activating gene 1 knockout (Rag1 -/-) mice, which are devoid of T and B lymphocytes, were g-irradiated with a myeloablative dose and then received the transfer of donor bone marrow (BM) obtained from Rag1 -/mice and Drd3 -/mice mixed in a 4:1 ratio Rag1 -/--to-Drd3 -/as described before [48]. Thus, after BM reconstitution, Drd3-deficiency was confined to T and B lymphocytes, bearing Drd3-deficient adaptive immune system ( Fig.…”
Section: Cns Autoimmunitymentioning
confidence: 99%
“…Pregnancy, which leads to a suppression of T cell function (Doria et al , ), is also associated with a low incidence of HIT (Fausett et al , ). Murine models have shown that T cells expressing both CD4 and CD40 ligand are required to generate anti‐PF4/heparin IgG antibodies (Zheng et al , ); however, these antibodies were not investigated for their potential to induce Fc‐receptor‐specific platelet activation and cause HIT. In typical antibody responses, follicular T H cells express CD40 ligand, which engages CD40 on cognate B cells to induce class switch recombination, germinal centre formation, and memory cell generation (Elgueta et al , ).…”
Section: Hit Has Features Of a T Cell‐dependent Antibody Responsementioning
confidence: 99%